4(2-1)-66=-5(2x+3)

Simple and best practice solution for 4(2-1)-66=-5(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2-1)-66=-5(2x+3) equation:


Simplifying
4(2 + -1) + -66 = -5(2x + 3)

Combine like terms: 2 + -1 = 1
4(1) + -66 = -5(2x + 3)

Multiply 4 * 1
4 + -66 = -5(2x + 3)

Combine like terms: 4 + -66 = -62
-62 = -5(2x + 3)

Reorder the terms:
-62 = -5(3 + 2x)
-62 = (3 * -5 + 2x * -5)
-62 = (-15 + -10x)

Solving
-62 = -15 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
-62 + 10x = -15 + -10x + 10x

Combine like terms: -10x + 10x = 0
-62 + 10x = -15 + 0
-62 + 10x = -15

Add '62' to each side of the equation.
-62 + 62 + 10x = -15 + 62

Combine like terms: -62 + 62 = 0
0 + 10x = -15 + 62
10x = -15 + 62

Combine like terms: -15 + 62 = 47
10x = 47

Divide each side by '10'.
x = 4.7

Simplifying
x = 4.7

See similar equations:

| (-x+5)(7x-14)=0 | | 60x=x-3x | | -5x-2=x+4 | | 90-4x=2x+8 | | 4x+2.5=12.5+2x | | 35+x=14 | | 4x+2.55=12.5+2x | | -11x-4=14-9x | | 23-3n= | | 8+9x=134-12x | | 4096-x=127 | | x^4+2=-5 | | 272p-6=9p+5 | | CMa=3+2q | | 3x+66=15 | | 8x+61=-27 | | 6x+55=-35 | | 2x+22=-12 | | 2x+40=12 | | 7-3y=5+4y+11-16y | | 2(x-x-5+2)=6 | | 6x^2+16x-20=0 | | -0.75-x=0.5 | | 4t+9=-8t+13 | | 4x^2-19x+23=-2x+8 | | 8j=69 | | x^2-x-6=3x-1 | | 8-(-9)=1 | | (2x+5)(x-6)=0 | | x^2+12+33=6 | | 3ax-2bx+7=21+x | | 9x^2-0.3x=0 |

Equations solver categories